Characterization of curcumin loaded gliadin-lecithin composite nanoparticles fabricated by antisolvent precipitation in different blending sequences. (December 2018) - Yang, Shufang; Dai, Lei; Sun, Cuixia; Gao, Yanxiang
Abstract: Anti-solvent precipitation is a most commonly means of fabricating food-grade nanoparticles, while the impact of the blending sequence on the formation of nanoparticles is still unclear. In this study, curcumin (Cur) loaded nanoparticles were fabricated by antisolvent precipitation method using gliadin and lecithin in different blending sequences. Compared to stepwise antisolvent precipitation (SASP), antisolvent coprecipitation (ASCP) was capable of improving delivery efficiency with smaller particle size, lower turbidity and higher encapsulation efficiency of Cur. Based on the results of zeta-potential and turbidity, ASCP exhibited the greater capability to allocate lecithin on the particle surface than SASP, which potentially resulted in the smoother surface of gliadin-lecithin-Cur nanoparticles in morphological observation. The Cur entrapped in the nanoparticles was confirmed by fluorescence spectrum analysis. The results from particle size, Fourier transform infrared and circular dichroism analysis revealed that Cur was interacted with gliadin and lecithin mainly through hydrogen bonding, electrostatic interaction and hydrophobic effects, and interpreted that ASCP was capable of remarkably changing the secondary structure of gliadin, which was beneficial for reduction of the particle size. An alternative advantage of ASCP was to protect Cur in the nanoparticles against UV irradiation and thermal treatment with higher antioxidant capacity than SASP. Therefore, ASCP possessed wide applications in delivering bioactive compounds and the blending sequence played an important role on the performance of delivery systems. Graphical abstract: Highlights: Antisolvent coprecipitation (ASCP) was firstly compared to other blending sequences. ASCP significantly promoted encapsulation efficiency of curcumin (Cur). ASCP increased stability of nanoparticles and Cur in nanoparticles. Blending sequences potentially influenced interactions among ingredients.